Is the profession of a programmer relevant? - Viunyk, A. V. (ТДАТУ, 2019)
Smartphones, tablets, smart watches, fitness bracelets, smart home control systems, drones (for example, cleaning robots) require a huge army of programmers. Its “soldiers” daily create new applications to make you comfortable.
Keywords: programmer; programming; automation